İmtiyazlı pay sahipleri özel kurulu - Aktaş, Betül (Galatasaray Üniversitesi, 2018)
Doktora tez konumuz olan imtiyazlı pay sahipleri özel kurulunun temel işlevi imtiyazların korunmasıdır. Bu doğrultuda, imtiyazlı pay sahiplerinin haklarını ihlal edebilecek nitelikte olan genel kurulun anasözleşme değişikliklerinde, yönetim kuruluna sermaye artırımı yetkisi verilmesi kararında ve kayıtlı sermaye sisteminde yönetim kurulunun yaptığı sermaye artırımında özel kurul onayı alınması gerekmektedir. Aksi takdirde alınan genel kurul veya yönetim kurulu kararı uygulanamaz. Özel kurul toplantısının yapılabilmesi bakımından aranan temel şartlardan biri, imtiyazlı pay sahiplerinin haklarını ihlal edebilecek nitelikte bir anasözleşme değişikliği veya yönetim kurulunun sermaye artırımı kararının alınmasıdır. Özel kurul kararının alınmadığı aşamada genel kurul kararı hukuken geçerli, fakat hukuki sonuçlarını doğurması özel kurul onayının varlığına bağlıdır. The basic function of the special committee of preference shareholders is to protect the preferences. In this respect, Art. 454 of the Turkish Commercial Code (TCC) regulates the approval of special committee for the amendments to the articles of association of the general assembly, which are in the nature of violating the rights of the preferred shareholders, authorization for capital increase for the board of directors and the capital increase in the registered capital system. Otherwise, the decision of the general assembly or board of directors cannot be applied. One of the basic conditions sought in order to be able to hold the special board meeting is to adopt an amendment in the articles of association or the capital increase decision of the board of directors. At the stage where the decision of the special board is not taken, the decision of the general assembly is legally valid but its legal consequences are subject to the approval of the special committee.
Keywords: Anonim şirketler; Commercial law; Joint stock company; Pay sahipleri; Privileged share; Shareholders; Special meeting; Ticaret hukuku; Turkish Commercial Code; Türk Ticaret Kanunu; Özel kurul; İmtiyazlı pay

Anonim ortaklıklar hukukunda özel denetim - Günay, Gözde Engin (Galatasaray Üniversitesi, 2018)
Anonim şirketlerde pay ve oy çoğunluğunu elinde bulunduranlar bir araya geldikleri zaman, hâkimiyeti elinde bulundurdukları için şirket yönetimini etkileyecek kararları alarak, kendi kararları doğrultusunda şirketi yönlendirebilirler. Çoğunluğu elinde tutanların gücü karşısında azlık ve münferit pay sahiplerinin korunması, onlara bazı bireysel haklar tanınması ile sağlanmaya çalışılmıştır. Çalışmamızın konusu Anonim Ortaklıklar Hukuku'nda Özel Denetim'dir. TTK'nin "pay sahibinin kişisel haklarıˮ ana başlığı ve V. numaralı özel denetim isteme hakkı alt başlığı altında TTK m.438 ve 444' da düzenlenen özel denetim isteme hakkı, anonim ortaklıkta önemli bir bireysel ortaklık ve azlık haklarından birisini oluşturmaktadır. Aydınlatıcı haklar olarak adlandırılan bilgi alma ve inceleme hakkı ile özel denetim isteme hakları; şirketin faaliyetleri, işlemleri, ekonomik durumu hakkında yeterli bilgiye sahip olmayan pay sahiplerinin, bu haklarını kullanarak daha bilinçli olmalarını sağlarlar. Bu iki hak, hem önleyici hem de telafi edici niteliktedir. According to Article 438, CO Art.697a, any shareholder may introduce a motion at the general meeting of shareholders calling for certain facts to be subject to a special examination by a special and independent searcher. The special examination has to be necessary for the exercising of the shareholders' rights. If the shareholders' meeting approves the motion, the judge (called upon by the Company or by shareholder) appoints the special searcher. If the general meeting does not approve the motion calling for the appointment of the appointment of the special searcher, shareholders who represent at least ten percent of the share capital or who represent shares with par value of one million Turkish Lira may request the judge to appoint a special searcher. The shareholders are legally entitled to the appointment of a special searcher if they credibly establish that corporate bodies have violated the law or the articles of incorporation and have thereby damaged company or shareholders. Special examination has a pre-condition for requesting, as per article TTK m.438, in order for a shareholder to request a special examination, that shareholder or any shareholder of the company should have duly consumed its right to information and examination. This is pre- condition for requesting the special examination
635031
Keywords: Anonim ortaklıklar; Anonim şirketler; Control; Denetim; Incorporated companies; Joint stock company; Private auditor; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Özel denetçi

Acentenin ücret hakkı - Teki̇n, Ufuk (Ankara Üniversitesi, 2018)
Ücret hakkı acentenin en temel hakkı olup Türk Ticaret Kanunu'nun 113 ila 116. maddeleri arasında düzenlenmiştir. Hangi işlemlerin acenteye ücret hakkı kazandıracağı 113. maddede yer almaktadır. Bu hükme göre acente doğrudan kendi katkısıyla kurulan işlemler sebebiyle ücrete hak kazanabileceği gibi, müvekkile daha önce kazandırdığı müşterilerle sonradan kurulan aynı nitelikteki işlemler sebebiyle de ücrete hak kazanabileceği ifade edilmiştir. Söz konusu hükme göre ayrıca acente, kendisine belirli bir bölge veya müşteri çevresi bırakıldığı takdirde, bu bölgede veya müşteri çevresiyle kendi katkısı olmadan kurulan işlemler sebebiyle de ücrete hak kazanabilecektir. Yine aynı hükme göre acente, bazı şartların varlığı halinde acentelik sözleşmesinin bitiminden sonra kurulan işlemler sebebiyle de ücrete hak kazanmaktadır. Acentenin ücrete hak kazanabilmesi için Türk Ticaret Kanunu m. 113'e göre ücrete hak kazandıran bir işlemin varlığına ek olarak, m. 114'te ifade edildiği üzere kurulan işlemin ifası da gerekir. İşlemin ifasıyla doğan ücret hakkı, doğumu tarihinden itibaren en geç üç ay içinde ve her halde sözleşmenin sona erdiği tarihte muaccel olur (m. 116). Acentenin, ücret istemi, muacceliyeti ve hesaplanması bakımından önemli olan bütün konular hakkında kontrol hakkı bulunmaktadır. Bu hak, onun bilgi alma, müvekkilin defter kayıtlarının suretlerinin gönderilmesini talep ve inceleme hakkı olmak üzere üç haktan oluşmaktadır. Çalışmamızın birinci bölümünde Türk ve karşılaştırmalı hukukta konunun düzenlenişi ile kavramsal çerçeve üzerinde durulacak; ikinci bölümünde ücrete hak kazanılmasının şartları ele alındıktan sonra üçüncü bölümünde ücretin belirlenmesi, hesaplanması ile ödenmesi ve ücrete ilişkin kontrol hakkı açıklanmaya çalışılacaktır. The right of remuneration, which regulated between the Articles 113 to 116 of the Turkish Commercial Code, is the most fundamental right of commercial agent. According to Article 113, it is stated that the commercial agent has the right of remuneration due to the transactions established by its own contribution. Commercial agent has the right of remuneration also for same quality of transactions, which established later with the former customer. According to same Article, the commercial agent may also be entitled to remuneration, whether it is left in a certain area or customer environment, due to the transactions established in this area or the customer environment even without its own contribution. It is pointed in the same Article that, commercial agent also has the right of remuneration due to transactions established after the end of the commercial agency contract in the presence of certain conditions. As indicated in the Article 114, it is also necessary to perform the transaction, which gives the commercial agent the right of remuneration. The remuneration arising from the performance of the transaction shall be due within three months at the latest from the date of birth and in any circumstances at the date on which the contract is concluded (Article 116). The commercial agent has the right to control all matters that are important in terms of remuneration, accural and calculation. That right includes, the right to demand information, copies of the commercial book records of the client and examination. In the first part of our work we will focus on the regulations and conceptual framework of Turkish and comparative law. After considering the conditions of the acquisition of the remuneration in the second part, it is aimed to explain the determination and the calculation of the remuneration, payment and the control right of commercial agent about the right of remuneration in the final section.
Keywords: Acenteler; Agents; Commercial law; Ticaret hukuku; Turkish Commercial Code; Türk Ticaret Kanunu; Wage; Wage account; Wage fixing; Ücret; Ücret belirleme; Ücret hesaplama